CEO DUALITY – AN EXPLORATIVE STUDY - Palanissamy, Ayyappan (European Scientific Journal, ESJ, 2015)
Corporate governance focus on a major issue to analyse whether the Chief Executive Officer of a firm should serve as board chairman is a debatable argument put forward in the changing world. In the wake of economic chaos globally with high-profile collapses of a number of large corporations in the recent years, has forced organisations to alter the composition of their corporate governance. The increase of pressure on corporate boards from enforcement agencies, as well as shareholders, challenges organisations to adopt new strategies and relook into their organisational structure. This article will look at literatures on various arguments put forward on the pros and cons of the CEO duality and its impact on firm effectiveness and performance. An analysis of theories of CG which includes Agency and Stewardship theories will be look into to have a clear picture on whether duality leads to firm effective performances or hinder performance. From the analysis, it can be concluded that there is no right or wrong board structure but generally shareholders and stakeholders are more inclined towards separation of the roles to promote independence and transparency. Although duality or separation may not have any direct linkage to firm performance, separation model promotes a healthier balance to the overall corporate governance of an organisation. A further research will be carried to look at the composition of the board in emerging corporations in gulf countries.